2020
DOI: 10.5090/kjtcs.20.042
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of 3-Dimensional Body Surface Scanning in the Evaluation of Patients with Pectus Carinatum

Abstract: Background: Radiographic modalities have been commonly used to evaluate pectus carinatum (PC), and compressive orthotic bracing is the most widely accepted treatment method. The aim of this study was to determine the efficacy of 3-dimensional (3D) body surface scanning as an alternative modality for the evaluation of PC. Methods: The medical records of 63 patients with PC who were treated with compressive orthotic bracing therapy between July 2017 and February 2019 were retrospectively analyzed. Using both 2-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A particular study was proposed by (Buonamici et al , 2019) who suggested a hybrid technique by analyzing both the depth image and the bi-dimensional image (provided by the red blu green depth, RGB-D, device) to detect the chest elevation during the VB treatment. Song et al (2020) studied the efficacy of the compression brace on a sample of 63 patients, evaluating severity before treatment and after 2 weeks of the compression brace usage, observing a statistically significant improvement of the pathology severity, which was also confirmed by Wong et al (2014) on a sample of 50 patients. On the other hand, the evaluation of efficacy for surgical treatments was studied in the cases of thoracic bar insertion for PE correction (Gomes-Fonseca et al , 2017; Port et al , 2019; Uemura et al , 2021) and surgical PC correction (Port et al , 2018).…”
Section: Reverse Engineering and Additive Manufacturing-based Innovat...mentioning
confidence: 76%
See 3 more Smart Citations
“…A particular study was proposed by (Buonamici et al , 2019) who suggested a hybrid technique by analyzing both the depth image and the bi-dimensional image (provided by the red blu green depth, RGB-D, device) to detect the chest elevation during the VB treatment. Song et al (2020) studied the efficacy of the compression brace on a sample of 63 patients, evaluating severity before treatment and after 2 weeks of the compression brace usage, observing a statistically significant improvement of the pathology severity, which was also confirmed by Wong et al (2014) on a sample of 50 patients. On the other hand, the evaluation of efficacy for surgical treatments was studied in the cases of thoracic bar insertion for PE correction (Gomes-Fonseca et al , 2017; Port et al , 2019; Uemura et al , 2021) and surgical PC correction (Port et al , 2018).…”
Section: Reverse Engineering and Additive Manufacturing-based Innovat...mentioning
confidence: 76%
“…The second category of targets is the main topic of Glinkowski et al (2009), Lain et al (2017), Uccheddu et al (2018), Kidane et al (2019), Deng et al (2020a, 2020b), Song et al (2020), Servi et al (2021). Perez et al (2006) analyzed the accuracy, resolution and repeatability of the VistusSmart (Human Solutions; Kaiserslautern), concluding that the 3D scanner is suitable for tracking the progression of the deformity and to analyze pre- and post-surgical pathological condition.…”
Section: Reverse Engineering and Additive Manufacturing-based Innovat...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, most practitioners favour other criteria such as depth measurements using an external gauge or 3D scanning [ 15–17 ]. The first measurement is readily and quickly accessible but its reproducibility is questionable.…”
Section: Introductionmentioning
confidence: 99%